Consumo de alcohol y bienestar psicológico en trabajadores de salud del primer nivel de atención en Iquitos, año 2025 - Vigil Tuanama, Enrique Amadeo (2025)
Objective: To determine the relationship between alcohol consumption and psychological well-being among healthcare workers at the primary level of care in Iquitos, 2025. Materials and methods: A quantitative, analytical, and cross-sectional study was conducted with 215 healthcare workers. The AUDIT Test was used to assess alcohol consumption, and the Ryff Psychological Well-Being Scale (29 items) evaluated the dimensions of psychological well-being. Data were processed using SPSS v25, applying correlation and Chi-square tests with a significance level of p < 0.05. Results: A total of 40.5% presented low-risk consumption, 26.0% risky consumption, 15.8% harmful consumption, and 17.7% probable dependence. A moderate level of psychological well-being predominated. A significant association was found between alcohol consumption and the dimensions of autonomy (p = 0.046) and purpose in life (p = 0.040). Likewise, age (p = 0.041) and working in another health center (p = 0.039) were associated with higher consumption levels. Conclusions: There is a high frequency of problematic alcohol consumption among healthcare workers. Although no significant relationship was found with overall psychological well-being, the autonomy and purpose in life dimensions showed relevant associations, highlighting the need to strengthen emotional well-being and preventive strategies within the health workforce.